Efisiensi Counter Electrode Dengan Pengurangan Pemakaian Platina Menggunakan Komposit Bahan Ramah Lingkungan Grafin Dan Carbon Nanotubes Untuk Aplikasi Dye Sensitized Solar Cells - fatiatun, fatiatun; Swasti, Intan Masruroh (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
Dye sensitized solar cells (DSSCs) are the most popular solar cells in the third generation. DSSCs have been widely developed as an alternative to silicon-based solar cells because of its easy manufacturing process, high efficiency, easy production costs, and environmental friendliness. Graphene and carbon nanotubes (CNTs) are promising materials to reduce the use of platinum (Pt) in counter electrode (CE) due to their excellent properties, such as thermal, electrical conductivity, and high surface area. One of the derivatives of graphene that is often used is reduced graphene oxide (rGO) which is produced from GO solution by a reduction process. GO was synthesized in an electrolyte containing surfactant by the electrochemical exfoliation method. The specially prepared sodium 1,4-bis(neopentyloxy)-3-(neopentyloxycarbonyl)-1,4-dioxobutane-2-silphonate (TC14) surfactant was used in GO synthesis. The CE thin film of TC14-rGO/CNTs/Pt hybrid shows the highest efficiency values (0.0594%) with Jsc, Voc, and FF of 0.176 mA/cm2, 0.622 V, and 0.464, respectively. This was believed due to the conjugated network in CNTs acts as a connecting cable between the TC14-rGO layers and as a vacancy filler, the high electrical conductivity value and the larger surface area also cause faster electron movement, making these properties important in DSSC performance. The FF value which is also the highest in the TC14-rGO/CNTs/Pt hybrid samples as CE is also influenced by its structure. The high surface area of CNTs and TC14-rGO in the TC14-rGO/CNTs/Pt hybrid samples exhibited important properties for generating dye after electron injection and led to a faster route of electron regulation during DSSCs processing. These findings indicate that Pt composited with environmentally friendly and inexpensive materials such as T14-rGO and CNTs can improve CE performance in DSSCs applications. Based on this, this research can be used as a basis for further research on the fabrication of carbon-based CE